The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4208/nmtma.2014.1313nm
|View full text |Cite
|
Sign up to set email alerts
|

Generalized and Unified Families of Interpolating Subdivision Schemes

Abstract: We present generalized and unified families of (2n)-point and (2n -1)point p-ary interpolating subdivision schemes originated from Lagrange polynomial for any integers n > 2 and p > 3. Almost all existing even-point and odd-point interpolating schemes of lower and higher arity belong to this family of schemes. We also present tensor product version of generalized and unified families of schemes. M oreover error bounds betw een limit curves and control polygons of schemes are also calculated. It has been observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…ese schemes have been introduced by [2][3][4][5][6]. e other types of subdivision schemes produce shapes which do not pass through the initial data.…”
Section: Introductionmentioning
confidence: 99%
“…ese schemes have been introduced by [2][3][4][5][6]. e other types of subdivision schemes produce shapes which do not pass through the initial data.…”
Section: Introductionmentioning
confidence: 99%
“…They also worked on subdivision regularization, in which they showed that unified frame work can work well for both curve fitting and noise removal. They generalized unified families of interpolating subdivision schemes of 2n-point and (2n − 1)-point p-ary which generate Lagrange's polynomial for n ≥ 2 and p ≥ 3, presented in [21]. In 2013, Younus and Siddiqi [22] established an algorithm based on Quaternary-point for (m > 1) approximating subdivision scheme which has high smoothness and small support.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al [11] introduced a scheme with multi-parameters in 2014. Mustafa et al [12] introduced the families of interpolating schemes with parameters in 2014. In 2017, Feng et al [13] presented a family of non-uniform schemes with variable parameters.…”
Section: Introductionmentioning
confidence: 99%